Rancang Bangun Alat Penyuling Minyak Atsiri Tumbuhan Nilam Metode Distilasi Air dan Uap - Hilda Porawati; Ari Kurniawan (Jurnal INOVATOR, 2019)
Indonesia is the largest supplier of essential patchouli oil on the world market. Patchouli essential oil cant hold or bind the fragrance of other fragrance ingredients so that the smell is longer lasting. Patchouli plant essential oils have a good chance because demand is always increasing population and the habits of the people tend to use cosmetics and fragrances as one form of people’s lifestyles, then the need for perfume is increasing every year. Make distillatory essential oil patchouli plant with water and steam distillation method to produce essential oils from patchouli.  The method used is the water and steam distillation method according, this method of distillation can produce steam and heat which is stable because of the constan vapor. The results of  the design  of   this  distiller  can  produce  essential oils from  patchouli. The design of patchouli essential oil refining equipment, the method used is steamed, with a scale of 2 kg patchouli and 20 liters of water. The kettle tube is made from aluminum plate the size used is a diameter of 300 mm. the results of the design of the refiner can produce essential oils from patchouli. The essential oil refiner uses gas fuel.